Irradiation for the Safety and Quality of Home Style Frozen Snacks - Z Irawati; L Natalia; CM Nurcahya; F Anas; M Tampubolon (PPIKSN-BATAN, 2005)
There are to market frozen prepared meals for microwaving or conventional way of preparation. Such meals. which offer convenience growing trends in Indonesia, and lesser time preparation are available in the developed countries, either chilled with limited shelf-life or frozen for long term sale in supermarkets. Irradiation at pasteurization doses has a potential role in improving the microbiological safety and shelf-life of chilled-prepared meals. Medium doses of gamma irradiation, 3-7 kGy, applied to spring rolls, rissole and croquette, in combination with frozen state during irradiation, followed by storage at 5 ± 2°C, have been conducted in order to ensure the safety and quality of the products during storage. The three different snacks. six pieces each. were vacuum packed in a laminate pouch of Poliester/Aluminum foil/LLDPE followed by fteezing over night at -20°C prior to irradiation at cryogenic condition. Irradiation at a dose of 7 kGy could relatively maintain the quality of the products during three months of storage 5 ± 2°C, based on different parameters, such as microbiological assessments, some chemical characteristics, and organoleptic analysis using five hedonic scales.